Isolation and Characterization of a Molybdenum-reducing and Phenol-degrading Pseudomonas sp. strain Aft-9 in soils from Pakistan (Journal of Environmental Microbiology and Toxicology, 2025)
Bioremediation is a better alternative when other procedures, including physical or chemical ones, don't work to get rid of small levels of dangerous heavy metals and organic contaminants.  In this investigation, we found a bacterium that can remove molybdenum from soil that has been polluted.  The bacterium could grow on phenolic chemicals such phenol, benzoate, 2-napthol, and catechol. The best rate for the bacterium to change sodium molybdate to molybdenum blue (Mo-blue) is when the pH is between 6.3 and 6.5 and the temperature is between 25 and 30 °C.  In that order, glucose, fructose, and galactose were the best electron donors for helping molybdate reduction. It is also important to know the phosphate levels, which should be between 5.0 and 7.5 mM, and the molybdate levels, which should be between 15 and 20 mM. The Mo-blue that came out showed absorption spectra that were extremely similar to those of a phosphomolybdate that had been decreased. At 2 ppm, heavy metals mercury (II), silver (I), copper (II), and chromium (VI) reduced molybdenum reduction by 78.9%, 69.2%, 59.5%, and 40.1%, respectively.  Biochemical tests tentatively identified the bacterium as Pseudomonas sp. strain Aft-9.  This bacteria is useful for bioremediation since it can detoxify molybdenum and grow on poisonous phenolics.
Keywords: Bioremediation; Molybdenum; Molybdenum blue; Bioreduction; Phenol-degrading